Prognostic Value of CT Imaging-Based Tumor Volume in Patients With Non-Surgical Esophageal Squamous Cell Carcinoma - Kang, Ning; Fang, Yeying; Zhu, Huijun; Shi, Zhiling; Chen, Liuyin; Lu, YuShuang; Wang, Housheng; Lu, Jiamei; Liu, Wenqi; Hu, Kai (Frontiers in Oncology, 2021)
Background: The American Joint Committee on Cancer Tumor (AJCC-T) staging system for esophageal carcinoma (EC) patients based on the depth of tumor invasion is not applicable in some cases. This study aimed to assess the prognostic value of CT imaging-based tumor volume and its usefulness for T staging in patients with non-surgical esophageal squamous cell carcinoma (ESCC). Methods: We retrospectively reviewed the records of 158 ESCC patients from two hospitals. Tumor volume based on the CT imaging was calculated using the formula: V=πabc⁄6. Three cutoff points for tumor volume were obtained with the X-tile software. Overall survival (OS) was analyzed using the Kaplan-Meier method. The -2 log-likelihood ratio test and Akaike Information Criterion (AIC) value were evaluated to compare the AJCC-T staging system with the proposed T staging method. Results: The median tumor volume was 19.8 cm³ (range 1.01 to 319.5 cm³). The three optimal cutoff points of tumor volume were 12.7, 22.8, and 51.9 cm³, and the patients were divided into four groups named as proposed T1-T4 stages. The 3-year OS rates in patients with proposed T1 to T4 stage were 67.9%, 30.6%, 21.3%, and 5.3%, respectively. The -2 log-likelihood ratios of the AJCC-T stage and proposed T stage were 1068.060 and 1047.418, respectively. The difference in the AIC value between the two T staging systems was 18.642. Conclusion: CT imaging-based tumor volume was superior to the depth of tumor invasion for T staging in predicting the prognosis of non-surgical ESCC patient.